2018
DOI: 10.7196/samj.2018.v108i3.12961
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the South African sport supplement industry: ‘Whey’ overdue

Abstract: The South African sport supplement industry has experienced rapid growth in recent years. Despite the massive market demand, this industry remains poorly regulated. From raw ingredient contamination to label compliance discrepancies, the sport supplement industry is an area of growing concern and warrants further public debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The use of sport supplements with the aim to improve performance is an age-old tale that can be traced back to the third century BC, where evidence was found that the athletes of that era made use of substances that improved their sporting performance, with additional information identifying that supplement use was prevalent among Greek Olympians in 776 BC. [ 7 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of sport supplements with the aim to improve performance is an age-old tale that can be traced back to the third century BC, where evidence was found that the athletes of that era made use of substances that improved their sporting performance, with additional information identifying that supplement use was prevalent among Greek Olympians in 776 BC. [ 7 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…The increase in usage of sport supplements in high school athletes is a matter of concern as the sport supplements industry is often under scrutiny due to the poor regulation of the production and the labelling of the products. [ 7 ] This is evident is the article by the International Olympic Committee where it was found that athletes who have been tested for doping and had a positive test, made use of sporting supplements that may have contained small amounts of prohibited substances which were not indicated on the product’s list of ingredients resulting in unintentional doping. [ 21 ] This may support the ‘gateway hypothesis’ where athletes using sport supplements may use other substances that may be banned, such as anabolic steroids, in the future thereby opening the door for positive doping control tests and dangers to the athlete’s health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naidoo K thought that the athletic goods sector had grown quickly in recent years. There was a big market demand, but the industry was still poorly regulated [ 7 ]. Funk studied how to strengthen the consumption desire of sports consumers and determine the future trends of the sports industry [ 8 ].…”
Section: Literature Reviewmentioning
confidence: 99%